The Role of Therapeutic Communication in Government Policy and Covid-19 Coverage in the Media - Derivanti, Azizah Des (Department of Sociology, Universitas Nasional (Indonesia), 2020)
Health communication perspective which is commonly called therapeutic communication, has a principle that is contrary to the principle of the media